Emergence of the benefits and costs of grouping for visual search. (16th April 2018) - Wu, Rachel; McGee, Brianna; Rubenstein, Madelyn; Pruitt, Zoe; Cheung, Olivia S.; Aslin, Richard N.
Abstract: The present study investigated how grouping related items leads to the emergence of benefits (facilitation when related items are search targets) and costs (interference when related items are distractors) in visual search. Participants integrated different views (related items) of a novel Lego object via (a) assembling the object, (b) disassembling the object, or (c) sitting quietly without explicit instructions. An omnibus ANOVA revealed that neural responses (N2pc ERP) for attentional selection increased between pretest to posttest regardless of the training condition when a specific target view appeared (benefit) and when a nontarget view from the same object as the target view appeared (cost). Bonferroni‐corrected planned comparisons revealed that assembling the object (but not disassembling the object or no training) had a significant impact from pretest to posttest, although the ANOVA did not reveal any interaction effects, suggesting that the effects might not differ across training conditions. This study is one of the first to demonstrate the emergence of the costs and benefits of grouping novel targets on visual search efficiency.